(3cJGH aj GdWHs - (3SYjO Hf gHI Gddg Hf GdMSf GdQGhfOqj, CHh GdMSf, bWH GdOjf,J (B573 (3g` s
(3ChdgG (B:s
(3fHJOi HYhf Gddg JYGdi fcJH cJGH eLehYkG ai MceI GdCeQGV GdLSeGfjI bGd GdTjN Cf Chdi eG fWb Hg GddSGf GdMeO deOHQ GdCReGf s
(3BNQgG (B:s
(3heGA GdQeGf GdeR hGddHf jOgf GdehR hGddYGH Je GdcJGH HMeO Gddg JYGdi s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde ajg VHWs
(3HChdg agQS s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs